Reflections on the penal state in Brazil - Oliveira , Inaê Soares (Seven Editora, 2023)
This work aims to apprehend the elements that result from the passage from the welfare state in developed countries to what some contemporary authors, especially Loïc Wacquant, have come to call the Penal State. This model of State began to be defined and require systematic analysis and studies due to the unprecedented increase in the number of people incarcerated in the world, which signals punitive increases in mediations that concern social relations. However, some reflections around these analyses do not contemplate, at all, realities such as the Brazilian one, because some of its mechanisms are historical in the country. It is for this reason that this work seeks to point out some reflections regarding the debate on the Penal State in Brazilian society. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-148